Sound Hypostases of the Prayer of the Heart - Mirela MERCEAN-ȚÂRC (Studia Universitatis Babeş-Bolyai. Musica)
Song has always accompanied prayer in moments of worship of man throughout time. More precisely, the sound form of prayer has proven to be a necessity of expression, communication and communion with Divinity. The Prayer of the Heart or the Prayer of Jesus Christ is simple, non-canonical, being an exercise of asceticism for Christian believers. Its text is “Lord Jesus Christ, Son of God, have mercy on me, a sinner!”, and its continued repetition responds to the call of the Apostle Paul who urges us in his Epistles: “Pray without ceasing!”. The practice of this prayer is part of the hesychast tradition, it is attested both in the writings of the Holy Fathers and in the practice of some Athonite monks, to this day. The testimonies of the ones who delve into this prayer converge towards the idea of ordering the mind and connecting it with the heart and with Divinity. By transcribing and analyzing the melodic types with which the Prayer of the Heart was clothed sonorously, the work aims to highlight their circulation in the environment of Christians from the Romanian, Russian, Ukrainian and Belarusian churches, as well as the spread, respectively the adaptation of these songs to the musical specificity of Western culture. From modal, monodic songs, processed in rudimentary polyphonies with ison, to tonal songs, harmonized in the manner of the choral, from solo to choral interpretation, or accompanied by the electronic ison, the forms of representation of these prayers are of great variety, underlining the transition from a collective, oral, anonymous creation to that of the cult musical creation represented in this exhibition by two masterpieces by the Romanian composer Paul Constantinescu.